2022
DOI: 10.1021/acsabm.2c00620
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene-Based Slippery Surfaces Enable the Generation and Easy Retrieval of Tumor Spheroids

Abstract: Multicellular tumor spheroids are the most well-characterized organotypic models for cancer research. Generally, scaffold-based and scaffold-free techniques are widely used for culturing spheroids. In scaffold-free techniques, the hanging drop (HD) method is a more versatile technique, but the retrieval of three-dimensional (3D) cell spheroids in the hanging drop method is usually labor-intensive. We developed oil-coated polystyrene nanofiber-based reusable slippery surfaces for the generation and easy retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The WCA value of TrW is 86.8° (Figure S4), contributeing to the stability of the droplets, as indicated by previous studies. [ 18 ] Additionally, the 1 mm thickness of the TrW played a role in stabilizing the hanging drops, as previous studies have shown that the thickness of the hole can create a micro‐ring structure that aids in droplet stabilization. [ 15,16 ]…”
Section: Resultsmentioning
confidence: 99%
“…The WCA value of TrW is 86.8° (Figure S4), contributeing to the stability of the droplets, as indicated by previous studies. [ 18 ] Additionally, the 1 mm thickness of the TrW played a role in stabilizing the hanging drops, as previous studies have shown that the thickness of the hole can create a micro‐ring structure that aids in droplet stabilization. [ 15,16 ]…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that there is a difference in cytotoxicity, apoptosis, and cell cycle arrest of 7d between 2D and 3D systems. The 2D system consists of a monolayer, and the 3D system is a tumor spheroid. , There is a direct exposure of the cells to 7d in the case of the 2D system causing higher mortality and low IC 50 value when compared to the 3D system. In a 3D system, molecules need to cross the cell culture media effectively to reach the site of action.…”
Section: Resultsmentioning
confidence: 99%
“…The plate was cultivated for 10 days at 37 °C with 5% CO 2 . The developed cell spheroids were recovered by tilting the device to a 45° angle to the tissue culture wells filled with culture medium at each time point . The same procedure was also followed for the cytotoxicity assay as that of the 2D counterpart.…”
Section: Methodsmentioning
confidence: 99%
“…The final PC content in the membrane was determined by taking the membrane weight before and after the entrapment of PC. (Pulugu et al, 2022) These dried membranes were then used for the permeation studies of the model drug.…”
mentioning
confidence: 99%
“…The final PC content in the membrane was determined by taking the membrane weight before and after the entrapment of PC. (Pulugu et al, 2022) These dried membranes were then used for the permeation studies of the model drug. Samples were initially sputter coated with gold to obtain SEM images and were imaged at the accelerating voltage of 5 KV.…”
mentioning
confidence: 99%